Specifics of Relationships of Diligence Variables and Socio-Psychological Adaptation in International And Russian Students - G N Kameneva; M A Rushina; U N Anisimova (Peoples' Friendship University of Russia (RUDN University), 2014)
The article is devoted to the analysis of the peculiarities of the relations of the variables of diligence as a personality trait and socio-psychological adaptation of students. The presented results of an empirical study show both general and specific relationships for Russian and international students.